Power improvement of solar photovoltaic (PV) based on maximum power point tracking (MPPT) controller / Siti Munirah Ahmad Saad - Siti Munirah, Ahmad Saad (2018)
This thesis describe the analysis of a DC-DC boost converter for control photovoltaic power by using maximum power point tracking (MPPT) to maximize the photovoltaic array output power. The MPPT system is responsible for extracting the maximum photovoltaic power and transmitted to the load using boost converter which able to step up the voltage to required magnitude. This MPPT using perturb and observe algorithm, the algorithm are general algorithm and use as a code. The analysis using Matlab® and Simulink® simulation software. The methodology of this project to develop Photovoltaic model, maximum power point tracking (MPPT) and modern controller boost dc-dc converter application is performed in the system for analyse the state-space model. Modern controller was simulated in closed-loop condition which employs four types of controller such as state feedback, optimal, state feedback with feed forward and integral. The results from controller simulation are used to analyse transient response and overshoot percentage of output voltage from boost converter. The observer system when the output system is observable, a full state observer able to apply. Based on the findings, comparison has been made to summarize a controller with minimum error and better stability.